Characterization of the complete mitochondrial genome of Diodon hystrix with phylogenetic consideration. Issue 1 (1st January 2017) - Huang, Hai; Guang, Hong; Ma, Jun; Chen, Yan; Chen, Huapu
Abstract: In this study, the complete mitochondrial genome of Diodon hystrix was sequenced and analyzed. The mitochondrial genome is 16, 512 bp long and consists of 13 protein-coding genes, two rRNA genes, 22 tRNA genes and a control region. The gene order and composition of D. hystrix mitochondrial genome was similar to that of most other vertebrates. The nucleotide composition of the light strand in descending order is 28.69% of A, 31.64% of C, 23.66% of T and 16% of G. The NADH dehydrogenase subunit 6 (ND6) and 8 tRNA genes were localized in the light strand, and all other mitochondrial genes were encoded on the heavy strand. The phylogenetic analysis by maximum-likelihood (ML) method revealed that D. hystrix has the closer relationship to the Diodon holocanthus.